Pelaku Tindak Pidana Pencabulan Yang Dilakukan Oleh Anggota Keluarga - Yuniar, Dita; Titahelu, Juanrico Alfaromona Sumarezs; Corputty, Patrick (Faculty of Law Universitas Pattimura, 2025)
The crime of obscenity is a form of crime that has a serious impact on the victim, both physically, psychologically and socially. Juridical studies of criminal acts of sexual immorality are important to understand how Indonesian law regulates, protects and provides sanctions against perpetrators of these crimes. In the context of Indonesian criminal law, sexual abuse is regulated in the Criminal Code (KUHP) and special regulations such as the Child Protection Law. This article examines the elements of criminal acts of obscenity, the law enforcement process, and the obstacles faced by law enforcement officials in handling obscenity cases. Apart from that, efforts to protect victims and the role of the community in preventing this criminal act were also discussed. This study concludes with recommendations for improving regulations and more effective implementation of the law to provide justice for victims and prevent the recurrence of similar crimes. To find out the views of individualization theory, the views of individualization theory on criminal acts of sexual abuse and legal protection for children who are victims of family abuse. The research method in this research is normative juridical. The problem approaches used are the statutory approach, conceptual approach and case approach. From the results of this research, it can be concluded that sexual immorality is a crime which in Indonesian laws and regulations, if the elements of a criminal act of sexual immorality are met, criminal sanctions must be applied in accordance with the provisions of the applicable laws and regulations, namely Article 289 and supported by Law Number 23 of the Year. 2002 concerning Child Protection as a specialist leg of the Criminal Code. Meanwhile, legal protection for children who are victims of criminal acts of sexual abuse in accordance with statutory regulations stipulates the obligation to carry out rehabilitation efforts, namely in Article 6 of Law Number 31 of 2014 concerning Protection of Witnesses and Victims, as well as Article 69A of Law Number 35 of 2014. 2014 concerning Child Protection.